On Exponential Stability of Composite Stochastic Control Systems - Fakhreddin Abedi; Wah June Leong (Abstract and Applied Analysis)
New results for exponential stability in probability of a composite stochastic control system are established. The main results of this paper enable us to derive sufficient conditions for exponential stability in -th mean and almost sure exponential stability in probability of composite stochastic control system. Two numerical examples are given to illustrate the results.